The Influence of the Gallery Walk Type Cooperative Learning Model on Social Studies Learning Outcomes in Kurima State Middle School Students, Yahukimo Regency - Kanengga, Yop; Hartini, Hartini; Syarifuddin, Syarifuddin; Elpisah, Elpisah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to: 1) Describe student learning outcomes after learning using the Gallery Walk type cooperative learning model regarding Social Studies Learning Outcomes. 2) Knowing that there is a significant influence of the Gallery Walk type cooperative learning model on social studies learning outcomes. The research approach used is a quantitative approach, quasi experimental design, nonequivalent group post-test only design. The research population included class VII students of Kurima State Middle School, Yahukimo Regency with a sampling technique using purposive sampling so that a sample of 1 class was obtained as an experimental class and that also as a control class. Data collection techniques use tests and documentation. The data analysis technique uses the T test. The research results show: 1) The average value of learning outcomes for experimental class students is higher than the control class. 3) There is a significant influence of the gallery type cooperative learning model on social studies learning outcomes.